The communication efficiency of persons with profound intellectual disabilities - Chilińska-Pułkowska, Alicja (Interdyscyplinarne aspekty diagnozy i terapii logopedycznej, 2020)
The article has characterised the functioning at the level of communication efficiency of persons with profound intellectual disabilities in speach act and reception. The results of the studies, based on available diagnostic tools to help extract communication channels, form, thematic scope and the way messages are transmitted, are taken into account. Final analysis gives an image most of the communication behaviour forms which can be observed in a child with profound disability. Without undermining the need of individualisation of the diagnostic process of communication skills, the data obtained can be illustrative and focus therapists’ attention on specific signals which can be interpreted as communicative. Further interpretation of them always depends on the personal characteristics, situations, capabilities and preferences a person under charge. The subject considered in this article is the begining of a therapist’s path, including the speech therapist in improving the ability to communicate with a child with special communication needs. Creating a reliable diagnosis allows you to introduce actions that minimize lack of speech and present other effective forms of communication. It is the basis for introducing AAC actions which allow you to establish clear and relatively satisfying relationship with children and for them it will be helpful in expressing their needs and understanding the reality.